Evaluation of Design, Governance, and Implementation of Khelo-India University Games Policy: An Assessment through RIDIT - Merajuddin Faridi, Merajuddin Faridi; Md. Kamran Khan, Md. Kamran Khan; Adnan Khan, Adnan Khan; Iftikhar Ahmad Wani, Iftikhar Ahmad Wani; Saddam Hussain, Saddam Hussain (International Journal of Sport Studies for Health, 2026)
Objective: This study aimed to assess stakeholders’ perceptions of the effectiveness of policy design, governance, and implementation of the Khelo India University Games (KIUG) scheme. Methods: A quantitative survey design was used. A structured questionnaire was personally administered to administrators, coaches, and players who participated in KIUG 2024. A total of 100 participants (25 administrators, 25 coaches, and 50 players) were selected using mixed-method sampling: coaches and players were recruited through random sampling, while administrators were selected purposively due to their limited numbers. Data were analyzed using RIDIT analysis and the Kruskal–Wallis test. Results: Overall, responses from players, coaches, and administrators were largely consistent, with no significant group differences across survey items. The only exception was item PDGI-05 (satisfaction with the central government’s initiative to organize KIUG in addition to Zonal/All-India Intervarsity competitions), which showed a significant difference among groups. Participants generally expressed support for the KIUG policy and its implementation, particularly regarding the development and upgrading of sports infrastructure, promotion of competition and talent development, inclusiveness, and fostering a balanced system integrating education and sport. Conclusion: Findings indicate broad stakeholder support for the KIUG policy and its implementation in KIUG 2024, with limited divergence across stakeholder groups. Further research is recommended to deepen the understanding of KIUG policy design, governance, and implementation, and to examine these dimensions across settings and time